2006
DOI: 10.1103/physrevb.73.212415
|View full text |Cite
|
Sign up to set email alerts
|

Steplike magnetization of spin chains in a triangular lattice: Monte Carlo simulations

Abstract: A two-dimensional Ising-like model for a triangular spin-chain lattice, where each spin-chain is treated as a rigid giant spin, is proposed to investigate the magnetization of a triangular spin-chain lattice by Monte Carlo simulation. The simulations show the steplike evolution of the magnetization at low temperature against an external magnetic field, namely two steps above 10 K and four steps below 10 K, in quantitative agreement with experiments on a Ca 3 Co 2 O 6 compound. It is argued that the interchain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 21 publications
5
56
1
Order By: Relevance
“…Interestingly, such Y-type magnetism, with noncollinear spin pairs, can lead to multiferroicity in some compounds [16][17][18][19][20][21]. While in the Ising-spin limit, spins arranged in 2D triangular lattice can also form some exotic patterns [23][24][25]. For CaOFeS, the neutron experiment at 6 K identified an Ising stripe AFM order, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, such Y-type magnetism, with noncollinear spin pairs, can lead to multiferroicity in some compounds [16][17][18][19][20][21]. While in the Ising-spin limit, spins arranged in 2D triangular lattice can also form some exotic patterns [23][24][25]. For CaOFeS, the neutron experiment at 6 K identified an Ising stripe AFM order, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the 2D triangular-lattice Ising model [24][25][26][27] has been successfully used to study the magnetization behaviors 28 in the spin-chain system Ca 3 Co 2 O 6 . In the model with the NN and NNN AFM couplings, a six-fold degenerate single stripe state is developed at low T. 29,30 Earlier analysis has shown that the destruction of the state has to take place via a phase transition of first-order character.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 With half of Co ions replaced by Mn ions, Ca 3 CoMnO 6 consists of parallel 1D CoMnO 6 chains, aligned along the hexagonal c-axis and separated by Ca 2+ ions. It forms a triangular lattice in the ab-plane.…”
Section: Theory and Modelingmentioning
confidence: 99%